Analysis of phase interactions between heart rate variability, respiration and peripheral microhemodynamics oscillations of upper and lower extremities in human. (January 2022) - Tikhonova, Irina V.; Grinevich, Andrey A.; Tankanag, Arina V.
Graphical abstract: Highlights: Phase interactions between HRV, respiration and peripheral hemodynamics were studied. High significant coherence was obtained for all signal pairs at 0.1 Hz. There was high coherence for blood volume oscillations and HRV/respiration at ~0.3 Hz. There was low coherence for blood flow oscillations with HRV/respiration at ~0.3 Hz. The observed phase interactions were similar for upper and lower extremities. Abstract: Wavelet phase coherence (WPC) between heart rate variability (HRV), respiration, forearm/foot skin blood flow (SBFforearm and SBFfoot ) and finger/toe tissue blood volume (TBVfinger and TBVtoe ) oscillations were studied in healthy volunteers at rest. SBF was recorded from the outer surface of the right forearm and the dorsum of the right foot. TBV was registered on the right index finger and the right second toe. The significance of obtained WPC values was tested with surrogate method. The observed phase interactions between all analyzed signals were similar for upper and lower extremities. At heart rate frequency (~1 Hz) significant WPC (sWPC) was high for SBFforearm – SBFfoot and TBVfinger –TBVtoe pairs for the most subjects that are explained by cardiac output as the central mechanism of their generation. High sWPC values for HRV – SBFforearm, HRV – SBFfoot, HRV – TBVfinger, HRV – TBVtoe, SBFforearm – SBFfoot and TBVfinger – TBVtoe pairs were found at the frequency of 0.1 Hz for the most participants. We assumed the existence of similar mechanisms that regulate the peripheral microhemodynamics at this frequency. At respiration frequency (~0.3 Hz) sWPC values were high for HRV – TBVfinger/toe, RES –TBVfinger/toe and TBVfinger – TBVtoe pairs for the most persons. In contrary, at this frequency sWPC was low for HRV –SBF forearm/foot, RES – SBFforearm/foot and SBFforearm – SBFfoot pairs. The differences obtained may be associated with the contribution of sympathetic nerve activity to the control of the vascular tone of vessels under study.